Standard Operating Procedure: Fish in Supplementary Nutrition Programme (SNP) Assam, India - Ratha, Baishnaba; Shenoy, Neetha; Gichohi, Wanjiku (WorldFish, 2024)
This document outlines the Standard Operating Procedure (SOP) for integrating fish into the Supplementary Nutrition Programme (SNP) in Assam, India. It provides detailed guidelines for planning, implementation, and monitoring, including sourcing, preparation, distribution, and quality control of fish-based products. The SOP aims to enhance the nutritional value of SNP meals, address malnutrition among vulnerable populations, and ensure compliance with food safety and government standards.